Two-Stage Optimal Operation Management of a Microgrid Considering Electricity-Hydrogen Coupling Dynamic Characteristics - Liu, Xinrui; Zhong, Weiyang; Hou, Min; Luo, Yuqing (Frontiers in Energy Research, 2022)
The uncertainty and volatility of renewable energy generation lead to large amounts of abandoned electricity. The electricity-hydrogen coupling microgrid (EHCM) consists of the proton exchange membrane electrolytic cell (PEMEC), liquid organic hydrogen carrier (LOHC) hydrogen storage, proton exchange membrane fuel cell (PEMFC). The structure helps to increase the utilization of wind and photovoltaic power. The scheduling of an EHCM is very challenging. This paper proposes the optimal operation of a microgrid considering the uncertainty of wind speed, light, and the coupling of electricity and hydrogen. The electricity-hydrogen coupling model and hydrogen market model are constructed. The microgrid provides ancillary services to the grid while meeting hydrogen demand. The above model is solved using a two-stage optimization method with time scales of day-ahead and intra-day. Finally, taking the IEEE 33-node microgrid as an example, the effectiveness of the proposed model is verified. The results of the case show that the proposed method can obtain more benefits and reduce carbon emissions.